The Final Months of Massive Star Evolution from the Circumstellar Environment around SN Ic 2020oi - Maeda Keiichi; Chandra Poonam; Matsuoka Tomoki; Ryder Stuart; Moriya Takashi J.; Kuncarayakti Hanindyo; Lee Shiu-Hang; Kundu Esha; Patnaude Daniel; Saito Tomoki; Folatelli Gaston (IOP PUBLISHING LTD, 2022)
We present the results of Atacama Large Millimeter/submillimeter Array (ALMA) band 3 observations of the nearby type Ic supernova (SN) 2020oi. Under the standard assumptions on the SN-circumstellar medium (CSM) interaction and the synchrotron emission, the data indicate that the CSM structure deviates from a smooth distribution expected from the steady-state mass loss in the very vicinity of the SN (less than or similar to 10(15) cm), which is then connected to the outer smooth distribution (greater than or similar to 10(16) cm). This structure is further confirmed through the light-curve modeling of the whole radio data set as combined with the previously reported data at lower frequency. Because this is an explosion of a bare carbon-oxygen (C+O) star with a fast wind, we can trace the mass-loss history of the progenitor of SN 2020oi in the final year. The inferred nonsmooth CSM distribution corresponds to fluctuations on the subyear timescale in the mass-loss history toward the SN explosion. Our finding suggests that the pre-SN activity is likely driven by the accelerated change in the nuclear burning stage in the last moments just before the massive star's demise. The structure of the CSM derived in this study is beyond the applicability of the other methods at optical wavelengths, highlighting the importance and uniqueness of quick follow-up observations of SNe by ALMA and other radio facilities.